Purchase Intention in Online Travel Agents Influenced by Service Quality, Online Reviews, and Perceived Ease of Use Mediated by Brand Trust - Andriya Prabaja Putra; Christian Haposan Pangaribuan (Al-Makki Publisher, 2025)
This study aims to analyze the effect of service quality, online reviews, and ease of use on purchase intention on online travel agents (OTAs), with brand trust as a mediating variable. The focus of this research is on Traveloka as the main subject. Quantitative methods are used in this research, with data collection through questionnaires distributed to 150 respondents who are active OTA users. The data was processed using SmartPLS 3 for statistical analysis. The results showed that service quality has a significant positive effect on purchase intention, both directly and indirectly through brand trust. Ease of use has a positive impact on brand trust, but has no direct effect on purchase intention. Online reviews showed no significant effect on purchase intention or brand trust. This finding confirms that brand trust plays an important role in consumer decision-making when booking accommodation online. Service quality is a key factor that must be considered by OTA service providers to increase customer loyalty. This study confirms that service quality and ease of use have a positive effect on brand trust, which in turn increases purchase intention. In contrast, online reviews did not contribute significantly to the model. Recommendations for OTA providers are to improve service quality and user experience to build customer trust, while future research is recommended to explore other factors that might influence purchase intention in the context of OTAs.